Optical Link Fault Detection and Localization in Passive Optical Network Domain - Nadiatulhuda Zulkifli , Auwalu Usman , Mohd Rashidi Bn Salim , Kharina Khairi (International Journal of Advanced Science and Technology, 2020)
Optical link fault detection and localization are significant in the Passive opticalnetwork (PON) due to the passive nature of the network elements involved. A singlefailure in the optical link can resort to a huge amount of data loss in the network.However, deployment of fault detection and localization devices is extremely limited dueto the extra cost network operators need to pay and the reliability of the devices. PONfault monitoring solutions have been investigated by the researchers over the decades; thechallenges for these monitoring techniques are the cost and complexity of theirdeployment. Thus, this work proposes a technique for the detection and localization offault in the optical link of a PON Fiber-to-the-x (FTTx) network using optical reflectors.The real-time back-reflected signal from the reflectors in the network will be utilized todetermine the optical link with fault. Experimental results obtained show that multipleoptical link impairments can be detected and localized in the PON FTTx based networkin-service, over a distance of 20 km, in a cost-effective manner. Measurements from astandard Optical Time-Domain Reflectometer (OTDR) is used to prove the validity of ourtechnique